The Meditation and Recociliation in Terms of Buddhism : A Case Study of Public Prosecutors of Department of Civil Rights Protection and Legal Aid, Nong Khai Province - Phumek, Netipol; Wachirapanyo, Phramaha Daosayam (Journal of Graduate MCU KhonKaen Campus, 2022)
This research article The objectives were 1) to study the condition of problems and obstacles of public prosecutors; 2) to analyze the principles of mediation and conciliation in criminal cases in Thai law of public prosecutors; 3) to propose guidelines for applying mediation and conciliation in Buddhism. To protect rights and help people in law and execution Nong Khai Province Qualitative research was used by collecting data from 195 case studies between 2017 and 2021 and key information was provided by judges, public prosecutors, conciliators, investigative staff, lawyers, people who received rights protection. and helping the people in the law and legal execution of Nong Khai Province, amounting to 45 people The results showed that Problems and obstacles of the public prosecutor There are problems with the powers and duties of the Attorney General in reconciling criminal disputes. Settlement of mediation and conciliation The extent to which a criminal offense can enter the mediation process at the investigative stage Criminal cases are settled before being filed before the court or pending the adjudication of the court. Civil liability in connection with a criminal case in the enforcement of the prosecutor's compromise agreement The time limit stops in criminal prosecution of the victim or the prosecutor in cases where the prosecutor has successfully mediated and conciliated a criminal dispute and the parties enter into a conciliation agreement. The prosecutor has successfully applied the principles of mediation and conciliation in criminal cases in Thai law, namely the attitude, ability and experience, knowledge, expertise in the use of law, experience and qualifications of the public prosecutor. along with the principles of physical strength, the 5 Brahma Viharas, the 4 Prejudices, the 4 Noble Truths and the principle of yonisomanasikan thinking come as a guideline for solving problems and eliminating obstacles to mediation Make effective mediation negotiations.